The risk of later surgery at the anastomotic site following right hemicolectomy for Crohn's disease in a national cohort of 12 230 patients. Issue 1 (21st October 2020) - King, Dominic; Coupland, Benjamin; Dosanjh, Amandeep; Cole, Andrew; Adderley, Nicola J.; Reulen, Raoul C.; Patel, Prashant; Trudgill, Nigel J.
Summary: Background: Crohn's disease (CD) has a high‐risk of bowel resection and later surgery for recurrent disease. Recent guidelines recommend colonoscopy 6‐12 months following surgery to reduce further surgical intervention through medical therapy intensification. Aims: To investigate the risk of further surgery at the anastomosis following right hemicolectomy for CD. Methods: Hospital Episode Statistics were used to identify patients with CD and a right hemicolectomy between 2007 and 2016. Adherence to post‐resection colonoscopy guidance timing and risk of further surgery at the anastomosis were examined. Cox proportional hazards models assessed risk factors for further surgery. Results: 12 230 patients were identified: 45% male; median age 36 (IQR 26‐49) years. Median follow‐up was 5.9 (IQR 3.6‐8.6) years: totalling 74 960 person‐years. Median time to further surgery was 2.9 (IQR 1.2‐5.3) years. By 5 years 9% and by 10 years 16.9% of those with sufficient follow‐up had at least one further surgery involving the anastomotic site. Older, less deprived patients and those whose index surgery took place on an elective admission had a reduced risk of further surgery. The annual number of right hemicolectomies increased over the study from 1063 to 1317, driven by the increasing prevalence of CD. Overall, 78% of patients did not have a colonoscopy, as recommended, within 6‐12 months following index resection. Conclusions: Further surgery involving the anastomotic site remains common following index right hemicolectomy for CD. Post‐surgical colonoscopy was only undertaken in 22% of patients within suggested timeframes. Increased colonoscopy may lead to a reduced need for surgery if early optimisation of medical therapy is undertaken for recurrence.